2021
DOI: 10.1007/s11065-021-09495-3
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic Eye Movement in Mild Cognitive Impairment and Alzheimer’s Disease: A Systematic Review and Meta-Analysis

Abstract: Alzheimer’s disease (AD) is the leading cause of dementia, and mild cognitive impairment (MCI) is considered the transitional state to AD dementia (ADD) and other types of dementia, whose symptoms are accompanied by altered eye movement. In this work, we reviewed the existing literature and conducted a meta-analysis to extract relevant eye movement parameters that are significantly altered owing to ADD and MCI. We conducted a systematic review of 35 eligible original publications in saccade paradigms and a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 119 publications
(299 reference statements)
0
40
0
Order By: Relevance
“…Notably, when we compared the AS latency of correct saccades in patients with MCI to HC, there was no significant difference between the groups. We previously showed that in PS/AS block administration, PS latency did not reliably distinguish between patients with MCI and age-matched controls, but AS latency was significantly different between the groups ( Opwonya et al, 2021 ). The differences in saccade latency suggest that latency differences between patients with MCI and HC are more pronounced in the PS interleaved and AS block modes, indicating a possible effect of the mode of administration (blocks vs. randomly interleaved).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, when we compared the AS latency of correct saccades in patients with MCI to HC, there was no significant difference between the groups. We previously showed that in PS/AS block administration, PS latency did not reliably distinguish between patients with MCI and age-matched controls, but AS latency was significantly different between the groups ( Opwonya et al, 2021 ). The differences in saccade latency suggest that latency differences between patients with MCI and HC are more pronounced in the PS interleaved and AS block modes, indicating a possible effect of the mode of administration (blocks vs. randomly interleaved).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that PS/AS paradigms could distinguish controls from patients with MCI using latency and error saccade parameters ( Opwonya et al, 2021 ). However, most studies have had few participants and used a blocked administration approach while conducting eye-tracking tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The measures of anti-saccade task were correlated with measures of inhibitory control, attention, working memory and self-monitoring 3 . Also, abnormal eye movement control has commonly seen in patients with brain disorders, including Alzheimer’s disease 5 7 , mild cognitive impairment 8 10 , Parkinson’s disease 11 13 , frontotemporal dementia 14 16 , autism spectrum disorders (ASD) 17 19 , ADHD 20 22 , and specific learning disorder (SpLD) 23 25 . Some emerging studies have provided some support for the efficacy and potential of eye-tracking-based training as a cognitive intervention 26 40 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also demonstrated that the saccade kinematics and the measurements of saccade paradigms can be useful in clinical diagnostics of neurological diseases (Leigh and Kennard, 2004;Ramat et al, 2007), including movement disorders (Termsarasab et al, 2015;Waldthaler et al, 2021;Fukushima et al, 2017), psychiatric diseases (Bittencourt et al, 2013;Morita et al, 2020), and neurodegenerative diseases (Antoniades and Kennard, 2015;Opwonya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, the visual paradigms and saccade measurements have been extended to the clinical means of investigation, evaluating different neurological disorders (Gooding and Basso 2008; Das et al 2022; Everling and Fischer 1998; Leigh and Kennard 2004; Ramat et al 2007), including movement disorders (Termsarasab et al, 2015; Waldthaler et al, 2021; Fukushima et al, 2017), psychiatric diseases (Bittencourt et al 2013; Morita et al 2020), and neurodegenerative diseases (Antoniades and Kennard 2015; Opwonya et al 2021), and were proposed as an early behavioural measurement for these disorders. In those studies, patients showed significant errors while performing the tasks.…”
Section: Introductionmentioning
confidence: 99%